The phenomenon of the romantic lyrical cycle. On determinants of cyclicality – The Crimean Sonnets, Vade-mecum and Les Fleurs du mal - Igliński, Grzegorz (Papers in Linguistics, 2021)
This article focuses on the determinants of cyclicality characterising the lyrical cycle in general and, in particular, romantic cycles, which are all marked by the motif of the road but also by the “suggestion of autobiographic nature”. Examples used to illustrate the analysis comprise works by Adam Mickiewicz (The Crimean Sonnets), Cyprian Norwid (Vade-mecum) and Charles Baudelaire (Les Fleurs du mal). Although so different in their thought and imagery layers, they are linked by the topos of wandering, which represents an interpretation of human condition. The analysis places emphasis on such elements that could indicate cyclicality and influence cohesion of the entire cycle as: dedication, motto, numbering of the poems (sometimes disregarding the first poem treated as the prologue), the work’s title and the title of a series of texts in that work (which may or may not have their own, separate titles), genre (e.g. sonnet), composition framework, mini-cycles (sub-cycles), “cyclic bundles” (e.g. pillar-poems separating mini-cycles), central group, supreme subject and supreme recipient of the cycle (which are not equivalent to the specific subject and recipient of an individual poem). Moreover, the presentation attempts to define the type of cyclic setup presented by the selected works of Mickiewicz, Norwid and Baudelaire depending on the level of cohesion of the cycle structure and autonomous nature of the links that form it.